Microbiological Examination and Determination of the Risk of Caries Development in a Patient with Esophageal Reflux Disease - K. Filipi; Z. Halačková (Czech Dental Chamber, 2010)
The main oral manifestation of gastroesophageal reflux disease is dental erosion. The very few studies have evaluated the damage and changes of soft, periodontal tissues and microbial flora. The aim of this study was to measure mutant streptococci and lactobacilli counts as predisposing factors to dental caries using Dentocult SM® and Dentocult LB® tests.The results showed lower counts of Streptocococcus mutans and lactobacilli, that means lower predisposing factor to dental caries. These results suggest that demineralization of hard dental tissues is without cariogenic plaque.